(untitled) (World Economics and Finance Bulletin, 2024)
The research aimed to present the requirements of the International Financial Reporting Standard IFRS9, as well as to indicate the extent to which private Iraqi banks, the research sample adhere to the requirements of the content of the International Financial Reporting Standard IFRS9. In light of this, the research reached a set of conclusions, the most prominent of which is the need to apply the International Financial Reporting Standard IFRS9 financial instruments in the banks selected as the research sample, as well as the presence of great challenges facing banks in particular and economic units in general with regard to the substantial increases in credit risks with regard to the initial recognition of the application of expected credit losses According to the IFRS 9 standard, and that the application of the International Financial Reporting Standard IFRS9 achieves an increase in loan loss provisions that result in more useful provisions, especially when credit conditions deteriorate.